Detection of Copy Number Variation by SNP-Allelotyping. (March 2015) - Parker, Brett; Alexander, Ryan; Wu, Xingyao; Feely, Shawna; Shy, Michael; Schnetz-Boutaud, Nathalie; Li, Jun
Abstract Charcot-Marie-Tooth disease type 1A (CMT1A) is caused by an abnormal copy number variation (CNV) with a trisomy of chromosome 17p12. The increase of the DNA-segment copy number is expected to alter the allele frequency of single nucleotide polymorphism (SNP) within the duplicated region. We tested whether SNP allele frequency determined by a Sequenom MassArray can be used to detect the CMT1A mutation. Our results revealed distinct patterns of SNP allele frequency distribution, which reliably differentiated CMT1A patients from controls. This finding suggests that this technique may serve as an alternative approach to identifying CNV in certain diseases, including CMT1A.